Clinical reasoning assessment through medical expertise theories: past, present and future directions - Boushehri, Elham (Med J Islam Repub Iran, 2015)
Exploration into the concept of "medical expert" dates back to more than 50 years ago, yet yielding three leading theories in the area of clinical reasoning, namely, knowledge structure, hypotheticdeductive, and dual process. Each theory defines "medical expert" in a dissimilar way. Therefore, the methods of assessment through which the experts are identified have been changed during the time. In this paper, we tried to categorize and introduce some widely used tests for identification of experts within the framework of existing main theories. Implementation of the proposed categorization for providing future assessment tools is discussed.